2022
DOI: 10.3390/ijms23137172
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctive Analyses of BSA-Seq and BSR-Seq Unveil the Msβ-GAL and MsJMT as Key Candidate Genes for Cytoplasmic Male Sterility in Alfalfa (Medicago sativa L.)

Abstract: Knowing the molecular mechanism of male sterility in alfalfa is important to utilize the heterosis more effectively. However, the molecular mechanisms of male sterility in alfalfa are still unclear. In this study, the bulked segregant analysis (BSA) and bulked segregant RNA-seq (BSR) were performed with F2 separation progeny to study the molecular mechanism of male sterility in alfalfa. The BSA-seq analysis was located in a candidate region on chromosome 5 containing 626 candidate genes which were associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
0
0
0
Order By: Relevance
“…BSA-seq has been widely used to map the QTL of target traits in crop species [18,36] Some studies have reported that BSA-seq can be combined with other techniques to fur ther reveal key functional candidate genes, such as with RNA-Seq, BSR-seq, and the link age mapping approach [17,18,20]. In this study, the combination of BSA-seq and SSR markers was used for the first time to identify QTL conferring resistance to RFS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BSA-seq has been widely used to map the QTL of target traits in crop species [18,36] Some studies have reported that BSA-seq can be combined with other techniques to fur ther reveal key functional candidate genes, such as with RNA-Seq, BSR-seq, and the link age mapping approach [17,18,20]. In this study, the combination of BSA-seq and SSR markers was used for the first time to identify QTL conferring resistance to RFS.…”
Section: Discussionmentioning
confidence: 99%
“…At present, with the development of sequencing technologies and the availability of reference genome sequences of rice, bulked segregant analysis with whole genome resequencing (BSA-seq) is considered an efficient and cost-effective method to rapidly locate genomic regions containing genes or QTLs affecting target traits [17,18]. This method has been successfully used in several plant species, including Oryza sativa [18,19], Medicago sativa L. [18], Cucurbita pepo [20], and Zea mays [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, BSR analysis generally requires a high-quality reference genome, which reduces its efficiency in species with complex genomes. Thus, the combination of BSA and BSR takes advantage of both methods to improve the accuracy and efficiency of mapping [30][31][32].…”
Section: Introductionmentioning
confidence: 99%